2007
DOI: 10.1063/1.2717525
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface enrichment of Co in Si (100) at initial stages of growth at room temperature: A study by high-resolution Rutherford backscattering

Abstract: Study of interdiffusion between thin Y-Ba-Cu-O films and MgO substrates by applying Rutherford backscattering spectrometry combined with scanning tunneling microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
(20 reference statements)
1
15
2
1
Order By: Relevance
“…1a shows, we can fit our experimental data very well in this way, which we cannot do otherwise. It should be noted that this result is different from results for Co growth on Si(100) at room temperature by our group [13] (see also Fig. 2c) and by Meyerheim et al [9], where only an incorporation of Co in the top-most Si layer was observed.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…1a shows, we can fit our experimental data very well in this way, which we cannot do otherwise. It should be noted that this result is different from results for Co growth on Si(100) at room temperature by our group [13] (see also Fig. 2c) and by Meyerheim et al [9], where only an incorporation of Co in the top-most Si layer was observed.…”
Section: Resultscontrasting
confidence: 54%
“…• C. For direct comparison with the low temperature growth data presented here, Co HRBS spectra of a sample grown at room temperature [13] (22…”
Section: Resultsmentioning
confidence: 99%
“…This is different from the case of Co growth on Si (100) at room temperature, where -besides Co at the surface -pronounced subsurface enrichment of Co was observed [23]. In the case of 0.0325 MLs of Fe on Si (100), pronounced oscillations in the Fe concentration were observed due to preferential occupation of every second Si layer with Fe atoms.…”
mentioning
confidence: 54%
“…[1][2][3][4][5] The formation of interfacial compounds plays an important role in the structure and physical properties of metallic films supported on semiconductor substrates. [1][2][3][4][5] The formation of interfacial compounds plays an important role in the structure and physical properties of metallic films supported on semiconductor substrates.…”
Section: Introductionmentioning
confidence: 99%